2007
DOI: 10.1158/0008-5472.can-06-2236
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Chain Fv Diabody against Human Leukocyte Antigen-A Molecules Specifically Induces Myeloma Cell Death in the Bone Marrow Environment

Abstract: Cross-linked human leukocyte antigen (HLA) class I molecules have been shown to mediate cell death in neoplastic lymphoid cells. However, clinical application of an anti-HLA class I antibody is limited by possible side effects due to widespread expression of HLA class I molecules in normal tissues. To reduce the unwanted Fc-mediated functions of the therapeutic antibody, we have developed a recombinant single-chain Fv diabody (2D7-DB) specific to the A2 domain of HLA-A. Here, we show that 2D7-DB specifically i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 54 publications
2
24
0
Order By: Relevance
“…As reported previously, 27,28 this led to robust actin aggregation in the cytoplasm and eventually induces cell death (Figure 5b). To clarify the signaling pathway involved in this effect, we first examined the phosphorylation pattern of signal-associated factors such as p44/42 MAPK, STAT3 and Akt in the presence of C3B3 with or without stimulation of interleukin-6 or IGF-1.…”
Section: Rpmi8226supporting
confidence: 83%
See 1 more Smart Citation
“…As reported previously, 27,28 this led to robust actin aggregation in the cytoplasm and eventually induces cell death (Figure 5b). To clarify the signaling pathway involved in this effect, we first examined the phosphorylation pattern of signal-associated factors such as p44/42 MAPK, STAT3 and Akt in the presence of C3B3 with or without stimulation of interleukin-6 or IGF-1.…”
Section: Rpmi8226supporting
confidence: 83%
“…26 Previously, we have demonstrated that HLA class I molecules are overexpressed in MM cells and that a recombinant single-chain Fv diabody against this molecule efficiently crosslinks HLA class I and induces rho-mediated actin aggregation, which leads to MM cell death without effector function. 27,28 In this study, we generated a new diabody specific to HLA class I molecule (C3B3) and investigated its potential on cancer stem cell-like fraction of MM cell lines and primary MM cells, focusing on the regulation of b-catenin and pluripotency-associated transcription factors.…”
Section: Introductionmentioning
confidence: 99%
“…28,29 We found that ligation of CD1d in the surface of the KMS11-CD1d cell line also induces considerable cell aggregation compared with KMS11-vector control ( Figure 4A). …”
Section: Cd1d-induced Apoptosis Is Associated With Cell Aggregation Amentioning
confidence: 94%
“…No correlation between extent of cell death and level of CD1d expression was found (r 2 ϭ 0.081). The reason for this is not clear, but lack of correlation between HLA level of expression and cell death has been also observed with the anti-HLA class I diabody remain 2D7 29,34 and may reflect the increased affinity of the corresponding mAb. Therefore, consistent with a role of CD1d in myeloma cell survival, its ligation on the surface of myeloma cell lines and primary myeloma cells induces cell death.…”
Section: Ligation Of Cd1d Induces Cell Death In B and Plasma Cellsmentioning
confidence: 99%
See 1 more Smart Citation